Influence of Experimental Provisional Cements Containing Zeolite, Bone Hydroxyapatite and Linoleic Acid on Bond Strength of Composite to Dentin In Vitro - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2010)
Purpose To evaluate the dentin bond strength of a composite resin material after the removal of two experimental cements containing zeolite, bone hydroxyapatite and linoleic acid, and one conventional glass ionomer cement in tended as provisional cements Materials and Methods Forty extracted caries free, erupted permanent third molars were used Experimental provisional cements containing zeolite and bone hydroxyapatite (BHA) and one conventional glass ionomer cement (GIC) were placed on the dentin surfaces and covered with tinfoil Cement covered dentin surfaces were stored in distilled water at 37 degrees C +/- 2 degrees C for seven days After this period, temporary cements were mechanically removed dentin sur faces were rinsed in distilled water and dried with an air syringe before adhesive application Dentin bonding agent was applied according to the manufacturer s instructions and the adhesion test was performed according to ISO TR 11405 Results The following shear bond strengths for the composite material were obtained no treatment applied (control group 4) 17 30 +/- 1 37 MPa provisional cement containing BHA (group 2) 15 03 +/- 3 44 MPa, GIC (group 3) 14 13 +/- 2 85 MPa provisional cement containing zeolite (group 1) 11 29 +/- 2 71 MPa The difference between groups 1 and 4 the control group was significant, where as the statistical analysis showed no significant difference between the control and BHA groups (ANOVA, Tukey s, p > 0 05) Conclusion In clinical applications where the previous application of provisional cements is necessary, material choice may influence the bond strength of the subsequent composite resin restoration
Keywords: bone hydroxyapatite; linoleic acid; provisional cement; shear bond strength zeolite; ZINC OXIDE-EUGENOL; GLASS-IONOMER CEMENTS; SILVER-ZEOLITE; TISSUE CONDITIONER; CALCIUM HYDROXIDE; FATTY-ACIDS; RELEASE; RESIN; BIOCOMPATIBILITY; DIFFUSION